Transformasi Kompetensi Literasi Bahasa Inggris Melalui Strategi Tense Visual Dan Direct Instruction Bagi Siswa Daerah Terpencil: Studi Kasus Di Sman Ii Aesesa, Ntt - Edelbertus Witu (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Through initial observations and interviews with local English teachers, three main problems were identified: fragmented grammar comprehension, limited vocabulary, and strategic and time management weaknesses. The goal of this activity was not only to improve test scores but also to restructure students' thinking about English texts. Practical contributions from this activity include the availability of a Visual Tenses learning model that converts abstract rules into easily recognizable patterns, as well as the introduction of a digital evaluation system to bridge the technological literacy gap. The community service program at SMAN II Aesesa has successfully achieved its goal of improving students' English competency. The synergy between the Direct Instruction method, grammar visualization strategies, and digital-based evaluation has proven effective in bridging the gap in educational access in remote areas. The 35% average increase in scores is empirical evidence that English learning difficulties at the high school level are being addressed not caused by low intelligence, but rather a lack of tactical learning strategies.